Extracellular Vesicle-Mediated Processes in Cardiovascular Diseases (2018)
It is long known that many cells can shed extracellular vesicles, small membrane-enclosed cell fragments. Although the existence of extracellular vesicles has been recognized for many years, researchers are only beginning to understand their physiologic significance. Several recent studies have demonstrated that extracellular vesicles released from cells serve as a mode of cellular communication. They can carry diverse molecular payload (e.g. nucleic acids, bioactive lipids and proteins) to distal recipient cells. Extracellular vesicles can be classified into three major groups; microvesicles, generated by budding of the plasma membrane, exosomes, consisting of cytoplasmic compartments released by exocytotic processes and apoptotic bodies, that are shed by cells undergoing programmed cell death. All these types of extracellular vesicles can be found in a variety of biologic specimen and their numbers, distribution and composition might serve as biomarkers for numerous disorders, including cardiovascular disease. Although extracellular vesicle-mediated processes are currently best characterized in the field of cancer biology and neurobiology, evidence is accumulating that extracellular vesicles play a key role in the pathophysiology of diabetes, thrombosis, inflammation and vascular calcification. In this Research Topic, we welcome original research from basic science reports to clinical studies as well as overview contributions that advance our understanding of extracellular vesicle-related processes in the field of vascular biology. We also strongly encourage methodology papers (either reviews for various methods or reports of new methods). Such articles may encompass research on microvesicles, exosomes and apoptotic bodies from leukocytes, platelets and cardiovascular cells as effectors or markers of physiologic and pathophysiologic processes in cardiovascular inflammation, calcification and remodeling. Submissions on molecular mechanisms of vesicle release as well as on nanoparticles for drug-targeting, cancer cell-derived vesicles or vesicles derived from other tissues will be considered in as far as related to the specialty section Atherosclerosis and Vascular Medicine, of Frontiers in Cardiovascular Medicine.